Optimization of Plasmodium vivax infection of colonized Amazonian Anopheles darlingi - Andrade, Alice Oliveira (2023)
Ministério da Saúde do Brasil/DECIT/CNPq Fundação Bill & Melinda Gates FAPERO ICEMR MMV FAPEAM CAPES CNPq